2016
DOI: 10.1111/hepr.12659
|View full text |Cite
|
Sign up to set email alerts
|

lincRNA‐p21 inhibits invasion and metastasis of hepatocellular carcinoma through Notch signaling‐induced epithelial–mesenchymal transition

Abstract: lincRNA-p21 was downregulated in HCC and lincRNA-p21 overexpression contributed to the inhibition of tumor invasion through mediating Notch signaling induced EMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 36 publications
1
55
0
Order By: Relevance
“…Osteoblasts are implicated in the incidence and progression of osteoporosis [35]. Many lncRNAs are regulated by osteoblasts, including the lncRNA repertoire and lncRNA-p21 [36,37]. DLL3 is an upregulated gene of the Notch signaling pathway, which is also regulated by osteoblast activity [15,38,39].…”
Section: Figure 14mentioning
confidence: 99%
“…Osteoblasts are implicated in the incidence and progression of osteoporosis [35]. Many lncRNAs are regulated by osteoblasts, including the lncRNA repertoire and lncRNA-p21 [36,37]. DLL3 is an upregulated gene of the Notch signaling pathway, which is also regulated by osteoblast activity [15,38,39].…”
Section: Figure 14mentioning
confidence: 99%
“…Its expression has been shown to be downregulated in prostate cancer [258], NSCLC [374] and HCC [255]. LincRNA-p21 has been shown in HCC to inhibit EMT via Notch signalling [255], but it plays many other additional regulatory roles [254,257,373,375]. …”
Section: Lncrnas and Emt: The Main Playersmentioning
confidence: 99%
“…HOTAIR and ZFAS1 have both been found to promote Notch signalling, while, as already mentioned, lincRA-p21 inhibits Notch signalling [255,423,424]. PVT1 activates Hedgehog signalling through indirectly regulating methylation of PTCH1 via miR-152 [328], while lncRNA-HH also activates Hedgehog signalling to promote EMT, possibly via promoting expression of GAS1, an enhancer of Hedgehog signalling [231,358].…”
Section: Lncrnas In Signalling Pathways Governing Emtmentioning
confidence: 99%
“…Mechanism study suggested that EMT-related protein E-cadherin, a tumor invasion suppressor in HCC, was identified as a putative gene target of miR-9 11. Besides, the previous study by the authors of this current paper showed that the expression of E-cadherin was upregulated by overexpression of lincRNA-p21 7. This has led to the speculation that lincRNA-p21 may regulate the expression of E-cadherin via mediating miR-9 expression, finally leading to the inhibition of HCC progression and development.…”
Section: Introductionmentioning
confidence: 60%
“…The most widely investigated lncRNAs in HCC include MALAT1, HOX antisense intergenic RNA H19, MEG3, MVIH and HULC 6. Besides, in the previous study, lincRNA-p21, a long intergenic noncoding RNA (lincRNA), was identified as an lincRNA that inhibits invasion and metastasis of HCC, and the underlying mechanism was found to be associated with the enhancement of epithelial–mesenchymal transition (EMT) 7. The aim of this study was to explore the further mechanism underlying the effects of lincRNA-p21 on EMT in HCC cells.…”
Section: Introductionmentioning
confidence: 93%